Pregnancy Following Cervical Tuberculosis (Journal of Chittagong Medical College Teachers' Association, 2015)
Incidence of urogenital tuberculosis is a raising concern worldwide specially in developing countries, in most cases, primary foci may not be identified either due to ignorance of the individual or her family may remain unaware about the seriousness or consequences. In this case a multiparous reproductive aged woman presented with repeated episode of post coital bleeding. Most of the attending Physician confused with hormonal disturbance and treated with hormone and others for months in outreach area. Once upon a time however she was referred to Gynae OPD and after inspection of cervix she was advised for inpatient admission for Examination Under Anaesthesia (EUA) and biopsy. Histopathology report revealed chronic granulomatous lesion of the cervix and ultimately she was diagnosed as a case of tubercular ulcer of the cervix. After successful treatment by antitubercular medication as per schedule, she was conceived and gave birth to a healthy term baby. Pregnancy following cervical Tuberculosis (TB) is a rare incidence and probably not reported in literature.JCMCTA 2015 ; 26 (1) : 55-58